RISIKO DAN REFLEKSIVITAS GAY TERHADAP KEKERASAN (Studi Kasus pada Komunitas Gay di Surakarta) - Vebrianti Rahayu; Argyo Demartoto (Universitas Sebelas Maret (UNS), 2019)
Gay is a minority group the existence of which is still unacceptable to the society. It puts the gay into a group vulnerable to violence risk. The objective of research is to study the risk and the reflexivity of violence in gay community in Surakarta. This qualitative with case study approach took place in Surakarta. The sampling technique used was purposive sampling one. The informant of research consisted of chairperson and administrators of Surakarta Gaya Mahardhika Foundation, gays becoming the victim of violence, community fellow members, and administrators of Mitra Alam Surakarta NGO. Data was collected through observation, in-depth interview, and documentation. To validate data, source triangulation was used. Technique of analyzing data used was Miles and Huberman’s interactive model of analysis with Ulrich Beck’s Risk Society theory. The result of research showed that violence risk encountered by gay in Surakarta included physical violence such as being thrown with sharp weapon, being struck and slapped; physical/emotional violence such as cynical and disliking view, expulsion, threat and negative stigma intended to gay organization; sexual violence such as sexual abuse conducted by police officer by touching the victim’s body organ; economic violence such as money and product expropriation by sexual partner; and verbal violence such as being insulted and mocked by some people on the street. The effect of violence consisted of physical effect such as bruise, gash, and pain still felt until today, and physical effect such as fear, trauma, discomfort and fidget, disappointment, resentfulness, anger, pique, and regret. The reflectivity of gay in dealing with violence included interacting or looking for acquaintance or partner more alertly and selectively; adapting, comporting; building intimacy an self-image by conducting positive activities within society; conducting homosexual activity more carefully such as fulfilling their sexual need in their known place rather than doing it in opened space that has been known by mass organization; and providing advocacy to the gay becoming the victim of violence.